The movement of 3D avatar in virtual reality game on human emotion behaviour - Basori, Ahmad Hoirul (Penerbit UTM, 2007)
The movement of 3D avatar is essential in virtual reality game in order to perform natural or emotional movement. Numerous researchers generally focus on movements from input such as: joystick, mouse, and keyboard. Other movement’s concepts come from artificial intelligence as part of improving interactivity. This chapter intends to offer a different method of controlling the virtual human characters movement that involves human emotion and haptic sensation known as human haptic emotion. The scheme engages human haptic emotion to control object life movements as a way to enhance simulation closer to reality and be more immersive. The movement of 3D avatar is a feature in virtual reality game which is usually controlled by mouse or keyboard, but recently it is controlled by artificial intelligence built from particular rule (Mocholi et al. 2006).